Responsabilidad penal por contaminación ambiental causada por incendio forestal y su incidencia con la tutela constitucional - Albán Gavilanes, Víctor Marcelo (2015)
This legal research, I performed in order to present a legal proposal to be reformed Art. 246 of the Penal Code of Integral concerning the part where typifies that agricultural or domestic burning by communities and small farmers are exempted within its territory. If these fires become uncontrollable and cause forest fires, the person shall be punished by culpable offense with imprisonment of three to six months worth, what is proposed in this research is to increase the punishment of one to three years. It is structured in six chapters: Chapter I refer to the Introduction, Problem Identification, Formulation and Definition of the Problem, Justification, General and Specific Objectives, Hypothesis, Variables, Resources, Materials, and budget used in research. CHAPTER II discusses the theoretical framework, the Background of Research, Groundwork, Doctrine, Jurisprudence, Law, Comparative Law and several comments. In CHAPTER III it is on the Methodology, about Determination Methods, as well as the Design Research, Population and Sample, Techniques and Tools for Research, Validity and reliability of the instruments and techniques of Procedure and data Analysis. CHAPTER IV consists of Analysis and Interpretation of Results regarding Hypothesis Research Hypothesis, Graphics and results surveys of citizenship, law Professionals, interviews Criminal Trial Judges and Officials of the Ministry of Quevedo’s Environment, the results obtained, the Hypothesis Testing, Reporting Research. CHAPTER V discusses the conclusions and recommendations. CHAPTER VI contains the Proposal, Title, Background, Rationale, General and Specific Objectives, Description of the Proposed Development, the Beneficiaries and Social Impact.